215k views
2 votes
Solve for f. -11f = 7(1 - 2f) + 5

2 Answers

6 votes

Answer:

f=

23/14

=1.643

Explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-11-(7*(1-2*f)+5)=0

-11 - (7 • (1 - 2f) + 5) = 0

14f - 23 = 0

3.1 Solve : 14f-23 = 0

Add 23 to both sides of the equation :

14f = 23

Divide both sides of the equation by 14:

f = 23/14 = 1.643

User Roman Svitukha
by
5.5k points
4 votes

Answer:

F = 4

Explanation:

−11f=7−14f+5

−11f=−14f+12

−11f+14f=12

3f=12

f=

​3

​12

​​

f=4

User Thibaultbl
by
5.3k points